2010
DOI: 10.3844/ajptsp.2010.125.132
|View full text |Cite
|
Sign up to set email alerts
|

Methamphetamine Regulation of Sulfotransferases in Rat Liver and Brain

Abstract: Problem statement: Sulfotransferases (SULTs) are important phase II drug metabolizing enzymes. They also regulate the biological activities of various hormones. To the best of our knowledge, psychostimulants regulation of SULTs is basically not studied except one article reported that Methamphetamine (METH) treatment induced rat amygdale rSULT1A1 mRNA 4.3 fold by using microarray method to identify a series of candidate genes after single-dose METH treatment. The psychostimulant METH is used to treat disorders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…In this study, the strength of rSULT2A1 induction by DA in rat liver was in agreement with that from in vitro study. Besides, it was demonstrated that methamphetamine, a structural analogue of DA, could induce the protein expressions of rSULT2A1 less than 2-fold, but with statistical significance, in rat liver, [24] which is consistent to our results as well.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In this study, the strength of rSULT2A1 induction by DA in rat liver was in agreement with that from in vitro study. Besides, it was demonstrated that methamphetamine, a structural analogue of DA, could induce the protein expressions of rSULT2A1 less than 2-fold, but with statistical significance, in rat liver, [24] which is consistent to our results as well.…”
Section: Discussionsupporting
confidence: 93%
“…One recent paper demonstrated that SULT1A3 could be induced by DA in vitro, indicating the role of SULT1A3 in CNS by protecting neuronal cells from DA toxicity [25]. Besides, our previous results showed that methamphetamine, a structural analogue of DA, could induce the expressions of rSULT2A1 remarkably in rat liver and brain [23,24]. Our recent data in vitro also revealed that the activity of SULT2A1 in HepG2 cells increased significantly after the treatment with DA, and the expression of SULT2A1 was significantly induced by specific D1 agonists (SKF-38393 and SKF 82958) that activating D1 signaling pathway selectively [26].…”
Section: Q2mentioning
confidence: 97%
“…This report showed that the treatment induced rat brain rSULT1A1 mRNA 4.3-fold in the amygdale. Later, our results indicated that METH induced rSULT1A1, rSULT2A1 and rSULT1E1 protein expression both in the rat liver and brain (Zhou et al, 2010). In this study, the effect of short- and long-term treatment of male rats with METH on rSULT1A1 and rSULT2A1 expressions in the cerebellum, frontal cortex, hippocampus, and striatum was studied.…”
Section: Introductionmentioning
confidence: 74%
“…Our previous results indicate that the anti‐cancer drug methotrexate (Maiti and Chen, ; Chen et al , , , ; Dutta et al , ) and all‐ trans ‐retinoic acids (Maiti et al , ) show induction activities toward various human and rat SULTs. Isoflavones (Chen et al , , ) and methamphetamine (Zhou et al , ) have also been shown to regulate rat SULTs expression.…”
Section: Introductionmentioning
confidence: 99%